SIMULASI PENDEKATAN FIXED RANDOM WALK DALAM ANALISIS DISTRIBUSI POTENSIAL LISTRIK PADA PELAT BERHINGGA - Supardiyono, ; Gagus Ketut Sunnardianto, (Matematika dan Sains, 2009)
The electric potential distribution was needed to determine the electrical field intensity and total charge in the condensator. This paper discussed the simulation of fixed random walk to analyze the electric potential distribution at unlimited plate using the matlab 7.1 program. The Procedure were carried out as follow: drawing configuration of two dimensional plate, determining the boundary condition, grid, and the sum random walk. Accuracy of the Monte Carlo method in fixed random walk approach were determined by the sum random walk (N), grid (Ä), and right of model system. The results obtained from the fixed random walk simulation closed with the analytic result. The presence of electrical potential value in interior plate area showed just there was one probably potential distribution for specific requisite limit of configuration.